2016
DOI: 10.1103/physreve.93.020701
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofBaTiO3nanoparticles on pretransitional effects in liquid crystalline dodecylcyanobiphenyl

Abstract: 2The pretransitional behavior of dodecylcyanobiphenyl (12CB, isotropic -smectic Asolid mesomorphism) with d=50nm BaTiO3 nanoparticles (NPs) linked to the cubic phase was monitored via temperature studies of dielectric constant. Tests were carried out in the isotropic, liquid crystal mesomorphic, and solid phases. For each phase transition the same value of the "critical" exponent ~ 0.5 was obtained, including nanocolloids. All phase transitions show the weakly discontinuous nature. The temperature metric of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…In the last decade liquid crystals (LCs) -nanoparticles (NPs) hybrid composites have become the hot topic in the soft matter and liquid crystals physics [1][2][3][4] . This is associated with their extraordinary metamaterial features, resulted from the mutually beneficial combination of unique semi-ordered fluids and solid nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade liquid crystals (LCs) -nanoparticles (NPs) hybrid composites have become the hot topic in the soft matter and liquid crystals physics [1][2][3][4] . This is associated with their extraordinary metamaterial features, resulted from the mutually beneficial combination of unique semi-ordered fluids and solid nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidences related to these issues for LCs+NPs composites are still very limited. In fact, the first experimental results focusing on critical exponents, the range of critical effects and the value of the discontinuity for weakly discontinuous phase transitions has reported only recently 1,4 . This was the case of dielectric constant behavior in BaTiO3 nanoparticles (non-ferroelectric) -dodecylcyanobiphenyl (12CB, isotropic -smectic A -solid mesomorphism) nanocolloid 1 .…”
Section: Introductionmentioning
confidence: 99%
“…We study thermotropic nematic LCs doped with NPs of volume concentration p in the diluted regime (i.e., p 1). We consider the two experimental observations addressed above, for which generic mechanism are not known: (i) non-monotonous ∆T(p) dependence [17,18], and (ii) p-driven crossover in S(p) dependence [19]. We first describe a possible mechanism yielding the non-monotonous ∆T(p) behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we consider cases where NPs induce a weak enough disorder, so that resulting LC structures exhibit qualitatively bulk-like behaviour, but quantitatively complex behaviour on increasing the disorder strength. We consider the phase and structural behaviour of thermotropic nematic LCs doped with NPs of volume concentration p. We first discuss recent experimental observations [17,18], which reveal nonmonotonous I-N temperature phase behaviour on varying p in the diluted regime (typically, p < 0.01). This was observed [17,18]…”
Section: Introductionmentioning
confidence: 99%
“…carbon nanotubes, silica microbeads, nanoparticles and various collides exhibit remarkable new physical phenomena. Experiments have shown that nanoparticles and ferroelectric nanoparticles can greatly enhance the physical properties of nematic and smectic liquid crystals [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%